Interstate and international trade of brazilian regions: an analysis using the gravity model - de Farias, Joedson Jales; Hidalgo, Álvaro Barrantes (Revista Econômica do Nordeste, 2016)
This paper analyzes the interstate and international trade of Brazilian regions in the period following trade liberalization. To carry out the analysis, the paper uses the gravity model methodology. The estimated trade models show that the border effect is still very significant for the foreign trade in Brazilian regions despite the process of economic openness that took place in the 1990s. The results show that the factors of resistance to the expansion of foreign trade still persist. Using a gravity model which considers the Brazilian states and the countries of the Southern Common Market (Mercosul) as a single market shows that then creation of this block increased trade in the region at the expense of other trading partners.